The stable isotope ecology of Pan in Uganda and beyond. Issue 10 (17th May 2016) - Loudon, James E.; Sandberg, Paul A.; Wrangham, Richard W.; Fahey, Babette; Sponheimer, Matt
Abstract : Stable isotope analysis has long been used to study the dietary ecology of living and fossil primates, and there has been increasing interest in using stable isotopes to study primate habitat use and anthropogenic impacts on non‐human primates. Here, we examine the stable carbon and nitrogen isotope compositions of chimpanzees ( Pan troglodytes ) from seven communities in Uganda across a continuum of habitat structure (closed to more open) and access to anthropogenic resources (no reliance to heavy reliance). In general, the hair δ 13 C, but not δ 15 N, values of these communities vary depending on forest structure and degree of anthropogenic influence. When integrated with previously published hair δ 13 C and δ 15 N values for Pan, it is apparent that modern "savanna" and "forest" Pan form discrete clusters in carbon and nitrogen isotope space, although there are exceptions probably relating to microhabitat specialization. The combined dataset also reveals that Pan δ 13 C values (but not δ 15 N values) are inversely related to rainfall ( r 2  = 0.62). We converted Pan hair δ 13 C values to enamel equivalents and made comparisons to the fossil hominoids Sivapithecus sp., Gigantopithecus blacki, Ardipithecus ramidus, and Australopithecus anamensis . The δ 13 C values of the fossil hominins Ar. ramidus and Au. anamensis do not cluster with the δ 13 C values of modern Pan in "forest" habitats, or with fossil hominoids that are believed to have inhabited forests. Am. J. Primatol. 78:1070–1085, 2016. © 2016 Wiley Periodicals, Inc.